The Impact of the Critical Thinking on Cognitive Building - Al Marri , Saad; Obaid , Hassan (Islamic Sciences Journal, 2023)
ABSTRACT The study aims to identify the impact of the critical thinking on human cognitive construction, highlight the concept of critical thinking, clarify its characteristics, interpret knowledge theories of critical thinking, identify the dimensions of critical thinking in cognitive construction, and identify critical thinking skills that must be available to learners, the importance of the research stems from its importance to highlight the critical thinking in cognitive development, achieving the desired renaissance of societies, and the ability of critical thinking to free students' thought from dependence on the ideas of others. This study relied on the descriptive approach and the analytical approach. Some of the important results were reached, including that critical thinking helps to reach the truth in a scientific way, and that critical thinking has two dimensions: the cognitive dimension and the emotional dimension, and that there are cognitive skills for critical thinking, such as: interpretation. The study showed that the critical thinker has major personal dimensions, including: understanding the rules of logic, and the ability to interpret. The study stated some recommendations, including: the necessity of teaching critical thinking and its importance in schools and universities, and preparing training courses for teachers and learners to qualify them to use critical thinking in the educational process.